Maternal Diets Deficient in Vitamin D Increase the Risk of Kyphosis in Offspring: A Novel Kyphotic Porcine Model. (7th March 2018) - Halanski, Matthew A.; Hildahl, Blake; Amundson, Laura A.; Leiferman, Ellen; Gendron-Fitzpatrick, Annette; Chaudhary, Rajeev; Hartwig-Stokes, Heather M.; McCabe, Ronald; Lenhart, Rachel; Chin, Matthew; Birstler, Jennifer; Crenshaw, Thomas D.
Abstract : Background: The purpose of this study was to explore the role of perinatal vitamin-D intake on the development and characterization of hyperkyphosis in a porcine model. Methods: The spines of 16 pigs were assessed at 9, 13, and 17 weeks of age with radiography and at 17 weeks with computed tomography (CT), magnetic resonance imaging (MRI), histology, and bone-density testing. An additional 169 pigs exposed to 1 of 3 maternal dietary vitamin-D levels from conception through the entire lactation period were fed 1 of 4 nursery diets supplying different levels of vitamin D, calcium, and phosphorus. When the animals were 13 weeks of age, upright lateral spinal radiography was performed with use of a custom porcine lift and sagittal Cobb angles were measured in triplicate to determine the degree of kyphosis in each pig. Results: The experimental animals had significantly greater kyphotic sagittal Cobb angles at all time points when compared with the control animals. These hyperkyphotic deformities demonstrated no significant differences in Hounsfield units, contained a slightly lower ash content (46.7% ± 1.1% compared with 50.9% ± 1.6%; p < 0.001), and demonstrated more physeal irregularities. Linear mixed model analysis of the measured kyphosis demonstrated that maternal diet had a greater effect on sagittal Cobb angle than did nursery diet and that postnatal supplementation did not completely eliminate the risk of hyperkyphosis. Conclusions: Maternal diets deficient in vitamin D increased the development of hyperkyphosis in offspring in this model. Clinical Relevance: This study demonstrates that decreased maternal dietary vitamin-D intake during pregnancy increases the risk of spinal deformity in offspring. In addition, these data show the feasibility of generating a large-animal spinal-deformity model through dietary manipulation alone.